Weather Indices for Designing Micro-Insurance Products for Small-Holder Farmers in the Tropics - Díaz Nieto, Jacqueline; Fisher, Myles; Cook, Simon; Läderach, Peter; Lundy, Mark (PLOS ONE, 2012)
Agriculture is inherently risky. Drought is a particularly troublesome hazard that has a documented adverse impact on agricultural development. A long history of decision-support tools have been developed to try and help farmers or policy makers manage risk. We offer site-specific drought insurance methodology as a significant addition to this process. Drought insurance works by encapsulating the best available scientific estimate of drought probability and severity at a site within a single number- the insurance premium, which is offered by insurers to insurable parties in a transparent risk-sharing agreement. The proposed method is demonstrated in a case study for dry beans in Nicaragua.